EVALUASI PELAKSANAAN PROGRAM LATIHAN SENAM DI KLUB SENAM SEMEN PADANG - Pitnawati Pitnawati; Damrah Damrah (Jurnal MensSana, 2019)
The issue of this study is the implementation of gymnastic training program that does not run well so that proper solution to solve this problem is demanded. The purpose of this study is to obtain accurate and objective information which can be taken into consideration in determining the implementation of the gymnastics training program that has been carried out, whether the training program can be continued, or must be revised, and can even be expanded to other clubs or regions. At the same time, it helps accountability and increases understanding of the phenomena that occur recently. This study employed an evaluation approach using the CIPP model developed by Stufflebeam, i.e. the evaluation model that observed the context, input, process and results (product). The results of this study showed that the gymnastics training program has not run optimally and needed improvement in several aspects, namely the increase of attention from the manager (FKSSP) to the policies that have been issued, improvement in the criteria for professional recruitment of trainers and athletes, improvement and procurement of national / international standard facilities, the use of varied training methods, increase of athletes' nutritional intake according to caloric needs, improvement of integrated monitoring systems and improvement of the welfare of trainers and athletes. All of these needs are none other than to continue the training process in order to obtain optimal performance improvements at the regional, national and international levels. Therefore, if the implementation of gymnastic training program runs well, then the components mentioned above need to be repaired and revised, so that gymnastic activities can perform well.